THE DEVELOPMENT AND VALIDATION OF AN ENGLISH SPEAKING ACHIEVEMENT TEST FOR 8TH GRADERS IN A SECONDARY SCHOOL IN HANOI = XÂY DỰNG VÀ XÁC TRỊ BÀI KIỂM TRA HỌC KÌ KĨ NĂNG NÓI MÔN TIẾNG ANH CHO HỌC SINH LỚP 8 TẠI MỘT TRƯỜNG THCS TẠI HÀ NỘI - Nguyễn, Vân Anh (2020)
Thanks to the trend of communicative language teaching and the introduction of the pilot English program, the role of speaking and speaking assessment is being highlighted in secondary school English education. However, speaking assessment instruments for secondary students are limited and not many of them are of good quality, due to the complexity of test development and validation. This empirical study is an attempt to design and evaluate the content validity of an English speaking achievement test for 8th graders based on conceptualized framework of test construction. To select the appropriate test content, observation of English 8’s textbook content and teaching practice, as well as teachers’ opinion collected by questionnaire had been conducted. A test was constructed at the end of the study. It was unveiled that responsive tasks were most appropriate to assess 8th graders’ speaking performance. The survey data gathered from testing experts afterwards has shown that the test content is valid in terms of relevance to objectives, duration, instructions and interaction amount. The rating scale and some tasks in the test, however, need further revisions to be more relevant to the course contents.